Alcohol Addiction, Alcohol Withdrawal Syndrome and Treatment - Supawat, Araya; Phunikhom, Kutcharin; Sattayasai, Jintana (Srinagarind Medical Journal, 2016)
Recently, there are many drugs for the treatment of alcohol addiction and alcohol withdrawal syndrome. However, several other drug candidates are currently evaluated by the researcher for a long term therapy and prevent relapse. The previous studies showed that the researcher were interested the efficacy of anticonvulsants drugs group according to variety mechanism of action to reduce alcohol addiction and alcohol withdrawal syndrome. Therefore, anticonvulsant medical plants may be promising candidates and modest pharmacological therapy for alcohol dependence.